Legal Tradition and Digital Innovation: Assessing the Position of e-Notary Products in Civil Disputes: Tradisi Hukum dan Inovasi Digital: Menakar Posisi Produk E- Notary pada Sengketa Perdata - Suryahartati, Dwi; Windarto; Lestari (Faculty of Law, Universitas Pasundan, 2025)
Changes in the development of digital technology have an impact on every aspect of life, including law. In Indonesia, the demand for electronic notaries has emerged as a form of innovation that promises efficiency. However, various concerns and challenges have emerged. This article discusses the issues faced by law and society as users of notary services. This article also discusses the philosophical and ethical aspects of law regarding the paradigm shift. Legal issues will be answered through an analysis of existing regulations and the legal theories that underlie them, as well as considering community responses. This article concludes that there has been a shift in the notary world that affects the way notaries work and the way society interacts with the law. Regulatory adjustments are needed that are able to adapt to accommodate electronic signatures, digital authenticity, and digital data management to realize effective electronic notaries and consider legal values ​​and ethics. Professional ethics in realizing integrity, transparency, and responsibility must be maintained and translated into a digital context. To achieve legal comparability in electronic notaries, it is important to consider the balance between service accessibility and strict levels of supervision and control.